2022
DOI: 10.3389/fphar.2021.764699
|View full text |Cite
|
Sign up to set email alerts
|

FGFC1 Selectively Inhibits Erlotinib-Resistant Non-Small Cell Lung Cancer via Elevation of ROS Mediated by the EGFR/PI3K/Akt/mTOR Pathway

Abstract: Non-small cell lung cancer (NSCLC) is one of the most common malignancies in the world. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have been used as a first-line treatment for patients harboring with EGFR mutations in advanced NSCLC. Nevertheless, the drug resistance after continuous and long-term chemotherapies considerably limits its clinical efficacy. Therefore, it is of great importance to develop new chemotherapeutic agents and treatment strategies to conquer the drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Most of the cytotoxic chemotherapy drugs are commonly used clinical anti-tumor chemotherapy drugs. Among the molecular targeted drugs, gefitinib, erlotinib, and osimertinib target the EGFR, and these three agents’ antitumor activities are affected by EGFR mutation status; whereas anlotinib is a multi-target protein kinase inhibitor ( Yan et al, 2021 ; Han et al, 10282021 ; Shen et al, 2020 ). Our results showed that the killing effect of anlotinib on LUSC cells is significantly stronger than that of gefitinib, erlotinib, and osimertinib.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cytotoxic chemotherapy drugs are commonly used clinical anti-tumor chemotherapy drugs. Among the molecular targeted drugs, gefitinib, erlotinib, and osimertinib target the EGFR, and these three agents’ antitumor activities are affected by EGFR mutation status; whereas anlotinib is a multi-target protein kinase inhibitor ( Yan et al, 2021 ; Han et al, 10282021 ; Shen et al, 2020 ). Our results showed that the killing effect of anlotinib on LUSC cells is significantly stronger than that of gefitinib, erlotinib, and osimertinib.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 1 induced mitochondria-mediated apoptosis, leading to increased ROS and reduced GSH. Thus, compound 1 caused apoptosis of erlotinib-resistant NSCLC cells [86,87]. In addition, compound 1 also inhibited the PI3K/Akt signaling pathway and the EGFR/PI3K/Akt/mTOR pathway.…”
Section: Effects On Cancer: Non-small Cell Lung Cancermentioning
confidence: 92%
“…Thus, it is necessary to discover new anti-tumor agents for treating NSCLC [85]. In 2022, Yan et al observed the effects of compound 1 on erlotinib-resistant NSCLC and explored the underlying mechanism [86]. NSCLC cells were sensitive to compound 1 with IC 50 = 7.45 ± 0.57 µM in vitro, especially for erlotinib-resistant NSCLC H1975 cells (IC 50 = 9.22 ± 0.84 µM); meanwhile, compound 1 was relatively safe for normal cells.…”
Section: Effects On Cancer: Non-small Cell Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we isolated a pyran-isoindolone compound FGFC1 ( Figure 1 ) with a molecular weight of 869 Da from a rare marine microorganism Stachbotrys longispora FG216, and characterized its fibrinolytic activity [ 36 , 37 , 38 ]. Based on these results, this study aims to further investigate the fibrinolytic activity of FGFC1 and its effect on fibrin network lysis in vitro.…”
Section: Introductionmentioning
confidence: 99%